2021
DOI: 10.1111/rec.13378
|View full text |Cite
|
Sign up to set email alerts
|

The present and future of grassland restoration

Abstract: Grasslands contribute greatly to biodiversity and human livelihoods; they support 70% of the world's agricultural area, but are heavily degraded by human land use. Grassland restoration research and management receives less attention than forests or freshwater habitats, although grasslands are critical for sustaining ecosystems multifunctionality and capacity to support biodiversity. In this article, we introduce a Special Issue which considers major trends and prospects in grassland restoration. We identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 50 publications
1
69
0
Order By: Relevance
“…However, grasslands may sometimes represent larger and more stable carbon sinks belowground than forests below-and aboveground combined (Dass et al 2018). The attention of the scientific community is also biased for forests, as a recent synthesis highlighted that nearly three times more papers are available in the Web of Science portal on the restoration of forests than grasslands (Török et al 2021). This bias is particularly expressed in the Global South, where grassland restoration is still in its infancy (Buisson et al 2021).…”
Section: Grassland Awareness Disparitymentioning
confidence: 99%
“…However, grasslands may sometimes represent larger and more stable carbon sinks belowground than forests below-and aboveground combined (Dass et al 2018). The attention of the scientific community is also biased for forests, as a recent synthesis highlighted that nearly three times more papers are available in the Web of Science portal on the restoration of forests than grasslands (Török et al 2021). This bias is particularly expressed in the Global South, where grassland restoration is still in its infancy (Buisson et al 2021).…”
Section: Grassland Awareness Disparitymentioning
confidence: 99%
“…Muller et al (2021) revealed the significantly less diversity and evenness in transformed grasslands since some species became more dominant. Meanwhile, Török et al (2021) concluded that disturbances promote species diversity by reducing the biomass of dominant grasses.…”
Section: Min Maxmentioning
confidence: 99%
“…Nonetheless, many semi‐natural grasslands have been converted into arable fields, overused, or simply abandoned (McDonald et al, 2016), making them the most threatened terrestrial habitats in Europe (Janssen et al, 2016) and worldwide (Humphries et al, 2021). This situation warrants immediate action to restore their beneficial services (Humphries et al, 2021; Janssen et al, 2016; Sojneková & Chytrý, 2015; Török et al, 2021).…”
Section: Introductionmentioning
confidence: 99%